The effects of puberty on associations between mood/personality factors and disordered eating symptoms in girls. Issue 9 (24th June 2021) - Vo, Phuong T.; Fowler, Natasha; Rolan, Emily P.; Culbert, Kristen M.; Racine, Sarah E.; Burt, S. Alexandra; Klump, Kelly L.
Abstract: Objective: Negative and positive urgency, anxiety, and depressive symptoms are significant factors of disordered eating (DE) symptoms in early adolescence through young adulthood. However, it is unclear how puberty—a critical developmental milestone that is associated with increased risk for DE symptoms—affects the relationship between these factors and DE symptoms, given that the role of pubertal status has rarely been considered in relation to these associations. Thus, the present study examined whether puberty moderates associations between mood/personality factors and DE in pre‐adolescent and adolescent girls. Method: Participants included 981 girls (aged 8–16 years) from the Michigan State University Twin Registry. Mood/personality factors, pubertal status, and DE were assessed with self‐report questionnaires. Results: Puberty significantly moderated associations between several factors (negative urgency, positive urgency, trait anxiety, depressive symptoms) and the cognitive symptoms of DE (e.g., shape/weight concerns, body dissatisfaction). Associations between mood/personality factors and cognitive DE were stronger in girls with more advanced pubertal status. By contrast, no significant moderation effects were detected for mood/personality‐dysregulated eating (e.g., binge eating, emotional eating) associations. Discussion: Findings identify pubertal development as an important moderator of mood/personality‐DE symptom associations, especially for cognitive DE symptoms that are known to predict the later onset of clinical pathology.